Graphene-based polymer nanocomposites in food packaging and factors affecting the behaviour of graphene-based materials: a review - Han, Lyn Foong; Z. A., Nur Hanani (Springer, 2022)
In recent years, there is a rapid advancement in the reinforcement of polymers using graphene-based materials (GBMs) such as graphene (thickness =  ~ 0.34 nm), graphene oxide (GO, thickness =  ~ 1.1 nm), and reduced graphene oxide (rGO). GBMs and their nanocomposites have been widely applied in numerous industries. Due to their remarkable properties, GBMs have also been incorporated in food packaging materials, providing efficient reinforcement in mechanical strength, barriers to light, water vapour, and gases, as well as antimicrobial and antioxidant properties, which are crucial in preventing food spoilage. This review aims to assess and summarize the published data in the use of GBMs in polymeric composites, particularly for food packaging. Then, we highlight the main factors that influence the behaviour and properties of the GBMs during the fabrication of the composites. Lastly, this review provides a brief summary of the current limitations as well as the food safety concerns regarding GBMs in food packaging.